2016
DOI: 10.1039/c6tc00410e
|View full text |Cite
|
Sign up to set email alerts
|

High thermoelectric performance of tellurium doped paracostibite

Abstract: Paracostibite (CoSbS) has recently been identified as a promising thermoelectric material, yet its full potential remains to be attained. By carrying out an optimization of the experimental parameters, we achieve a power factor as high as 2.7 mW m−1 K−2 at 543 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
26
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 32 publications
6
26
1
Order By: Relevance
“…We think that a small fraction of Se atoms may enter the Sb site, so as to create a slight increase in carrier concentration. Indeed, our previous DFT calculations have indicated that while Te Sb is the substitutional defect having the lower formation energy(0.2 eV at the VBM in Co rich condition), Se Sb is quite probable too(0.6 eV at the VBM in Co rich condition)7. This was confirmed by experimental results showing that Se can be used as a n-dopant, even though it remains less efficient than Te(10 20  cm −3 carriers with 2% Te doping versus 10 19  cm −3 carriers with 2% Se doping, the undoped materials showing a carrier density of 5 × 10 18  cm −3 ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We think that a small fraction of Se atoms may enter the Sb site, so as to create a slight increase in carrier concentration. Indeed, our previous DFT calculations have indicated that while Te Sb is the substitutional defect having the lower formation energy(0.2 eV at the VBM in Co rich condition), Se Sb is quite probable too(0.6 eV at the VBM in Co rich condition)7. This was confirmed by experimental results showing that Se can be used as a n-dopant, even though it remains less efficient than Te(10 20  cm −3 carriers with 2% Te doping versus 10 19  cm −3 carriers with 2% Se doping, the undoped materials showing a carrier density of 5 × 10 18  cm −3 ).…”
Section: Discussionmentioning
confidence: 97%
“…was about 0.5 at 873 K. Very recently, Chmielowski et al . could show through DFT point defect calculations, that Te substitution on the Sb site should theoretically be a significantly more efficient dopant than Ni substitution on the Co site7. Experiments validated this conclusion: It was indeed observed that a 4% Te doping allowed to reach an unpresented PF of 2700 μW.K −2 .m −1 at 543 K, which was maintained up to 730 K. To the best of our knowledge, this value is the highest reported for a polycrystalline chalcogenide material.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…However, the suldes identied for TE-application, e.g. 32 10,32,43,49 In an accompanying work on extrinsic doping of CoSbS, 32 we identify these defects as the Te Sb , Pd Co and Ni Co substitutional defects.…”
Section: Defect Thermochemistrymentioning
confidence: 99%
“…In Fig. 32 Finally a material specic comment on the bandgap of CoSbS. Note that the bandstructure calculations were tested on a very ne k-mesh of 34 Â 33 Â 17 points, however the S vs. T graphs did not change in comparison to that evaluated in the high-throughput procedure.…”
Section: Comments On Bandgapmentioning
confidence: 99%